Association of renal hyperfiltration with incidence of dyslipidemia: a nationwide retrospective longitudinal cohort study - Hyungjong Park; Min Kyoung Kang; Tae-Jin Song (PLoS ONE, 2025)
Background Individuals with chronic kidney disease (CKD) are often diagnosed with dyslipidemia, contributing to their cardiovascular risk. However, the relationship between renal hyperfiltration (RHF) and dyslipidemia remains unclear. Here, we aimed to examine the association between RHF and incidence of dyslipidemia. Methods We examined the data of 2,780,874 participants who underwent health examinations between 2010 and 2011 from the Korean NHIS-HEALS database. Renal function was assessed using estimated glomerular filtration rate (eGFR) levels that were calculated using the Chronic Kidney Disease Epidemiology Collaboration equation. The incidence of dyslipidemia was defined as the outcome. Dyslipidemia was characterized by meeting the following criteria: having at least one claim of International Classification of Diseases (ICD)-10 code (E78) with an anti-dyslipidemia agent prescription, claims of ICD-10 code (E78) occurring more than twice, a total cholesterol level ≥ 240 mg/dL, low-density lipoprotein cholesterol ≥ 160 mg/dL, triglycerides ≥ 200 mg/dL, or high-density lipoprotein cholesterol < 40 mg/dL. RHF was defined as having an eGFR > 120 mL/min ∙ 1.73 m2 defined by the eGFR range or being in the 10th decile of whole eGFR level. Results Over a median follow-up of 9.56 years, 2,243,502 participants with dyslipidemia were identified. The mean age of participants was 47.35 ± 13.96 years. In the multivariable Cox regression analysis, eGFR > 120 mL/min ∙ 1.73 m2 was associated with a decreased risk of dyslipidemia (HR: 0.35; 95% CI [0.34–0.36]). Furthermore, compared to the fifth decile, tenth (≥ 114.21) (HR: 0.47, 95% CI (0.46–0.48) eGFR deciles were significantly associated with a reduced incidence of dyslipidemia. Conclusions The general population with RHF may have a lower risk of incidence of dyslipidemia. The identified inverse association between RHF and dyslipidemia underscores its significance in risk stratification and preventive interventions in clinical practice.